Biomechanical outcomes of superior capsular reconstruction for irreparable rotator cuff tears by different graft materials-a systematic review and meta-analysis - Zhao, Xiaoxiong; Wen, Liang; Zhang, Bo; Jia, Jialin (Frontiers in Surgery, 2023)
Background： Irreparable rotator cuff tears (IRCT) are defined as defects that cannot be repaired due to tendon retraction, fat infiltration, or muscle atrophy. One surgical remedy for IRCT is superior capsular reconstruction (SCR), which fixes graft materials between the larger tuberosity and the superior glenoid. Patients and methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) criteria were followed for conducting the systematic review and meta-analysis. From their inception until October, 2022, Pubmed, Embase, and Cochrane Library's electronic databases were searched. Studies using cadavers on SCR for IRCT were also included. The humeral head's superior translation and subacromial peak contact pressure were the primary outcomes. The humeral head's anteroposterior translation, the kind of graft material used, its size, and the deltoid load were the secondary outcomes. Results: After eliminating duplicates from the search results, 1575 unique articles remained, and 20 papers were finally included in the quantitative research. In 14 investigations, the enhanced superior translation of the humeral head was documented in IRCTs. 13 studies found a considerable improvement following SCR, especially when using fascia lata (FL), which could achieve more translation restraints than human dermal allograft (HDA) and long head of bicep tendon (LHBT). Six investigations reported a subacromial peak contact pressure increase in IRCTs, which could be rectified by SCR, and these studies found a substantial increase in this pressure. The results of the reduction in subacromial peak contact pressure remained consistent regardless of the graft material utilized for SCR. While there was a statistically significant difference in the change of graft material length between FL and HDA, the change in graft material thickness between FL and HDA was not. The humeral head's anterior-posterior translation was rising in IRCTs and could be returned to its original state with SCR. In 5 investigations, IRCTs caused a significant increase in deltoid force. Furthermore, only one study showed that SCR decreased deltoid force. Conclusion: With IRCT, SCR might significantly decrease the glenohumeral joint's superior and anterior-posterior stability. Despite the risks for donor-site morbidity and the longer recovery time, FL is still the best option for SCR at this time.